Updated fine-scale location data for Blantyre district collected using a low-cost approach - Chifuniro Baluwa; Patrick Ken Kalonde; Upendo Lisa Mseka; Owen Tsoka; Kingsley Kajanga; Faith Chimphondah; Prince Time Matope Aaron; Francis Chimbalanga; Blessings Chiepa; Clinton Nkolokosa; Latif Ndeketa; Patrick Musicha; et al. (Scientific Data)
Abstract Knowing up-to-date geographical location of residential areas is crucial for understanding health-related factors and formulating targeted interventions. However, such data are often unavailable or resource-intensive to collect. This study employed low-cost approaches to map residential areas in Blantyre district, Malawi, which was severely affected by a cholera outbreak that lasted over a year (March 2022 to August 2023). We trained five data collectors using KoBo Toolbox and engaged Health Surveillance Assistants (HSAs) and motorcycle operators for precise location identification. We validated the data by involving key stakeholders from Blantyre District Health Office (DHO) and Malawi-Liverpool-Wellcome Research Programme (MLW). We successfully mapped 764 locations, demonstrating the effectiveness in rapidly mapping both residential and hard-to-reach areas. Associated costs were calculated based on MLW standard rates. This process highlighted the critical importance of accurate geolocation for public health research and interventions. Our study provides valuable spatial data and showcases the feasibility of cost-effective methods for gathering crucial public health information in resource-limited settings, potentially serving as a model for similar efforts globally.